Improving Students' Academic Performance Based on Islah Growth Mindset - Sundari, Pipit; Sulistyo, Heru; Cahyono, Budhi; Setiyarti, Tettie; Yusoff, Rushami Zien (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Islah-based growth mindset on students' academic achievement in Central Java, by considering the role of resilience in forming a growth mindset. The urgency of this study lies in the importance of overcoming the challenges of implementing a growth mindset in Indonesia, considering the inequality of access to education and culture that tends to emphasize the final result. The research sample consisted of 320 high school and vocational high school students in Central Java, selected using purposive sampling based on national achievement criteria, creativity, and self-development training. The hypothesis test results showed that resilience significantly affected the three dimensions of growth mindset. Islah Challenge Growth Mindset and Islah Grit Growth Mindset had a significant impact on students' academic achievement. Islah Attitude Growth Mindset: no significant effect. Managerial implications include the importance of developing students' mental resilience and perseverance in facing challenges and training educators to encourage a growth mindset. In addition, integrating Islam-based religiosity values ​​can strengthen the learning process and prepare students to face global changes with more resilience and innovation.